Assessment of the effect of UV and chlorination in the transformation of fragrances in aqueous samples. (April 2015) - Godayol, Anna; Gonzalez-Olmos, Rafael; Sanchez, Juan M.; Anticó, Enriqueta
Highlights: Chlorination/UV treatment were applied for elimination of fragrance allergens and musks in water. SPME followed by GC coupled to ion-trap MS allowed the determination of the target compounds. Only seven out of 17 compounds are eliminated (>75%) after 5 min irradiation time. Chlorine is not effective for the removal of galaxolide and tonalide. 15 UV transformation products were detected and chemical structures were proposed for five of them. Abstract: The removal and transformation of 15 common fragrance allergens and two polycyclic musks in water samples were studied using UV irradiation and chlorination treatments. The monitoring of the reaction was carried out by a HS-SPME method coupled to GC–MS analysis. Different behaviours were observed depending on the compound and the treatment applied. Elimination experiments showed that all target compounds were affected by at least one of the two treatments. A total of 15 UV transformation products were detected and chemical structures were proposed for five of them. In the chlorination experiments, only galaxolide and benzyl cinnamate transformation products were observed.